Letter to the editor concerning the article 'Association between rotavirus vaccination and risk of intussusception among neonates and infants: a systematic review and meta-analysis' (JAMA Netw Open. 2019;2(10):e1912458). Issue 10 (2nd October 2020) - Benninghoff, Bernd; Pereira, Priya; Willame, Corinne
ABSTRACT: A recent meta-analysis investigating the association between intussusception (IS) and rotavirus (RV) vaccination demonstrated an absence of risk up to 2 years after vaccination. Meta-analyses including only randomized clinical trials are inadequate to identify a potential increased risk of rare adverse events such as IS. The study conducted failed to discuss relevant limitations. Additionally, the safety profiles of newer RV vaccines, evaluated in clinical studies with limited sample size, were considered comparable with that of the well-established and widely used RV vaccines, RotaTeq and Rotarix. We, therefore, re-emphasize that extensive and updated evidence from post-marketing surveillance indicates a slight increased risk of IS, mostly within 7 days of RV vaccination, with a benefit/risk profile assessment in favor of RV vaccination.